Current-assisted direct Cu/Cu joining. (15th July 2015) - Shin, Chanho; Ma, Sung Woo; Lee, Jeong Hwan; Kim, Ki Bum; Suh, Minsuk; Kim, Namseog; Kim, Young-Ho
Abstract : Enhanced direct Cu/Cu joining by applying current was investigated. Joining was conducted at 240–300 °C for 10–50 min under 40 MPa. Current was applied to Cu wire during joining. Contact resistance of joints decreased and the fracture load of joints increased as the current increased. The joined region increased and the interface became less straight as the current increased. These results are ascribed to electromigration and joule heating effects. The enhanced diffusion contributed significantly to the joining of metals.